Managment of Superficial Infantile Capillary Hemangiomas with Topical Timolol Maleate Solution. (January 2015) - Rizvi, Syed Ali Raza; Yusuf, Faraz; Sharma, Rajeev; Rizvi, Syed Wajahat Ali
Abstract Capillary hemangioma is the most common benign tumor of eyelids and orbit in children. Recently, a topical beta blocker has been reported as an effective treatment for superficial capillary hemangiomas. We present a case report of two children having large capillary hemangiomas who responded well to topical treatment by 0.5% timolol maleate solution. After 12 months of treatment, the lesion has significantly reduced in size, thickness, and color in both cases. Thus, we conclude that long-term use of topical 0.5% timolol maleate solution is safe and effective in treating superficial capillary hemangiomas.